Switch actuators in process control: constraint problems and corrections - Mantz, Ricardo Julián (2015)
The paper deals with switch actuators in process control. The inclusion of a signal modulator required for commanding the actuator in proportional-integral-derivative (PID) controller structures is discussed. In particular, it is analysed how the restrictions of this modulator may worsen the well-known problems of process-input saturation, such as windup or loss of control directionality among others. From this analysis a simple correction methodology is proposed for simultaneously addressing constraints in both modulator and actuator. This methodology is easily implemented from feeding back a modulator signal and takes advantage of the wide knowledge existing in anti-windup techniques. Two examples (SISO and MIMO) are presented to assess the effectiveness of the proposed correction.